Dampak Covid-19 Terhadap Stabilitas Industri Keuangan - Nidya Oktavia Kurniawati; Wimber Jerry Panjaitan (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to examine the impact of the pandemic on the stability of the financial industry. After a disaster or disease outbreak in a region, the stabilization and recovery of various financial institutions will have a very important role in the overall economic recovery. Moreover, recently there has been a global disease outbreak (Covid-19) which has impacted the economies of various countries, including various financial institutions. This study uses a panel data approach and two estimation procedures, namely fixed effect and OLS to measure the impact of the pandemic on financial industry stability. Panel data used to measure the impact of natural disasters and disease outbreaks on the financial stability of the financial industry is fairly new to the research field, and provides valuable insights for policymakers and industry professionals. The results showed that natural disasters and outbreaks have a significant impact on the financial stability of the financial industry, and these have varying impacts depending on the type of disaster, country, and institution. From the findings of this study, the authors suggest that policymakers consider implementing new measures to mitigate the impact that will arise by improving risk management practices and increasing capital requirements for the financial industry. Future research is expected to focus on developing more comprehensive datasets to improve analysis and understanding of future impacts.